The attitude of population to the problem of social orphanhood - Ismagulova, S. Zh.; Kenzhakimova, G. A. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2017)
The article investigates the nature of social orphanhood, the conditions provoking him and approaches to prevention organization. The author reveals the main risk factors of social orphanhood. It is shown that the main risk factors can be systematized as follows: macro-level; an institutional, or an institutional-caused factors; microsocial, or individual level. It analyzed the concept of “orphan” as an acute social problem and solve it once and forever impossible. Consequently, the social policy of the state should be rebuilt by and is directed at improving the situation of the citizens. It is also noted that Kazakhstan is making great efforts to achieve global standards to improve the quality of life of their people, including in the field of protection of the rights and interests of children. Children need to be happy, to grow into full-fledged families have opportunities to develop their creative abilities, as well as protection in the face of the state. Identified and proved the main solution to the problem. It is shown that to solve the problem of prevention of social orphanhood in the country are developed and implemented programs of public services and their families, children who are subject to social orphanhood.Also, the primary task in the prevention of orphanhood in Kazakhstan – the priority of supporting and enhancing the status of social and healthy family, giving the society healthier, able-bodied, educated, literate generation. The author notes that the number of orphans in our country is increasing every year. The government spends a lot of activities aimed at improving the lives of children in institutions, developing legislation on new forms of placement of orphaned children. However, the solution to the problem of social orphanhood and depends on the activity of the whole society and each person in particular. It presents data of the Committee of Protection of the children rights of MES RK for 2015 concerning the situation of orphans and children left without parental care in Kazakhstan. Authors of the article has made an attempt to find out the population’s estimation of child abandonment increase, the degree of the respondents” concern about the fate of children without parental support, their attitude to a child’s placement to a state foster institution, their willingness to adopt an orphan, the level of the population’s knowledge about the problem of orphans and children without parental support and about the public authorities” activity in the solution of orphans” problems. The main results of the research are shown in the article.